Smilla, Anna og Alexandra – Videnskabskvinder i nyere dansk populærlitteratur - Nielsen, Kristian H.; Thomasen, Laura Søvsø (Slagmark - Tidsskrift for idéhistorie, 2018)
The article analyses three recent Danish crime novels, all of which introduce female main characters with a scientific background. In contrast to stereotypic male scientists, the female protagonists of the three novels all embody science as a kind of parallel text that reflects the individual characters of the protagonists, while also discussing issues pertaining to science itself and popular science.